The Effect of Voluntary Risk Management Disclosure and Risk Management Committee on Firm Value - Iman Harymawan; Dwi Ragil Rahmawati (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aimed to analyze the effect of voluntary risk management disclosure (VRMD) and the existence of a risk management committee (RMC) on firm value. Design/Methods/Approach: The research sample is companies listed on the Indonesia Stock Exchange for 2016, with 136 observations. The data obtained are based on annual reports. This study uses a quantitative approach with multiple linear analysis, with the help of the STATA 14 software program, as hypothesis testing. Findings: The results showed that voluntary risk management disclosure positively and significantly in the firm's value. The existence of the risk management committee had no significant effect on the firm's value. Originality: In this study, the researcher sees not only the existence of a risk management committee to measure risk management. However, the Voluntary Risk Management Disclosure score is rarely studied in Indonesia. Practical/Policy implication: This study has implications for investors to be more careful in analyzing the risks faced by the company so that investors avoid mistakes in making investment decisions and for the government to develop guidelines for disclosure of voluntary (non-financial) risk management and risk management committees.